Hubungan Pengetahuan Seks Pranikah dengan Perilaku Berpacaran Remaja di SMA YPPK Teruna Bakti Kelas XI - Cinthia Veronica Azmi (Journal on Education, 2023)
Teenagers' views on sex have shifted. Peralization globalization has resulted in the formation of culture and lifestyle, especially for young people of an age group who are very vulnerable to various changes and influences that come from outside. Dating with a variety of mild sexual behaviors such as touch, handrails, up to kisses and touch-touch sex which is basically the desire to enjoy and satisfy sexual urges also called heterosexuals.This study uses a quantitative method with a descriptive research design using a cross sectional approach. In this study the researchers wanted to describe the relationship between premarital sex knowledge and adolescent dating behavior in SMA YPPK Teruna Bakti XI class. This study shows that good pre-marital sex knowledge with positive dating behavior is 62 respondents (37.8%) while good pre-marital sex knowledge with negative dating behavior is 27 respondents (16.5%). And less knowledge of premarital sex with positive dating behavior as many as 53 respondents (32.3%) while lack of premarital sex knowledge with negative dating as many as 22 respondents (13.4%). After doing statistical calculations with the Spearman’s test, it was 0.011 with sig. (2- tailed) of 0.890 or ˃ 0.05 can be concluded that Ho is accepted and Ha is rejected, which means there is no relationship of premarital sex knowledge with adolescent dating behavior in SMA YPPK Teruna Bakti XI class